Self-Assessment of Russian Students’ Social Resistance - Semen D. Reznik (National Research Mordova State University, 2019)
Introduction. The problem of assessment and enhancement of social resistance of the Russian students is dealt with in the article. It focuses on the influence of a number of factors on the enhancement of social resistance among students under modern conditions. The authors give the first ever quantitative assessment of social resistance of students of higher education institutions in Russia. The purpose of the article is to examine the results of a study on the formation of social sustainability of students, to conduct on this basis an assessment of its level, to summarize the experience of developing and using special educational technologies that increase social sustainability and students' readiness for future professional activities. Materials and Methods. The following methods are used: questioning, expert poll, comparison, decomposition, and the group analysis. Data from more than 40 domestic and foreign sources are analyzed. The study population included students of Russian typical regional universities, the sampling totality comprised 400 students of 13 state-financed universities from 5 federal districts of the Russian Federation. The study also involved 36 skilled experts. Results. The research broadened the comprehension of the role and importance of the enhancement of student social resistance using special educational technologies. The coefficient of social resistance of Russian students (0.36) is not high enough. Also, the study revealed that for 50 % students the need of personal and professional development for successful employment in the futur e was a priority. Discussion and Conclusion. Conclusions are drawn concerning the need to realize the system of dedicated measures directed to increase the social resistance of the Russian students. The paper addresses students and teaching staff of Russian higher schools, education authorities as well as scientists studying problems of students’ evolvement.